Evaluating BMKG Public Information Services in Flood Disaster Areas Using ITO (Input-Throughput-Output) Model Approach - HS, Ira Marby; Meutia, Intan Fitri; Hermawan, Dedy; Yulianto, Yulianto (Eastasouth Institute, 2025)
Public information services from the Meteorology, Climatology, and Geophysics Agency (BMKG) play an important role in mitigating hydrometeorological disaster risks. This study analyzes the processes and factors that influence public information services at the Class I Radin Inten II Meteorology Station, especially in areas affected by flooding in Bandar Lampung City. With a qualitative descriptive approach, data were obtained through observation, interviews, and questionnaires involving 12 key informants and 41 respondents from the community. The results of the study indicate that although services have been digitized, the provision process is optimal, but regulations are needed as a legal umbrella for public service activities, and the need for audience understanding is still a challenge. These findings are the importance of optimizing communication strategies and collaboration with stakeholders to improve service effectiveness.